The correlation between premature rupture of membranes and first stage contractions with prolonged second stage of labor - Hurin'in, Nur Maziyah; Pujiati, Tutik (Borneo Scientific Publishing, 2025)
Prolonged second stage of labor significantly contributes to maternal and fetal morbidity and mortality, often associated with risk factors like premature rupture of membranes (PROM) and inadequate first stage contractions. This study aimed to analyze the correlation between PROM and first stage contractions with the incidence of prolonged second stage of labor among delivering mothers at UOBF Montong Tuban Health Center. A correlational analytic study with a cross-sectional design was conducted in December 2023. The sample included 77 delivering mothers (October-December 2023 period) selected via simple random sampling. Independent variables (PROM and first stage contractions) and the dependent variable (prolonged second stage labor) were assessed using medical record data. Data analysis utilized the Contingency Coefficient test (α=0.05). Results showed most respondents did not experience PROM (88.3%), had adequate first stage contractions (79.2%), and did not have prolonged second stage labor (77.9%). Statistical tests revealed highly significant correlations between both PROM (p=0.000) and first stage contractions (p=0.000) with prolonged second stage labor (p < 0.05). In conclusion, PROM and inadequate first stage contractions are significantly associated with prolonged second stage of labor at this facility. These findings can optimize risk screening, antenatal counseling, and labor preparation.